2022
DOI: 10.1007/s10433-021-00632-8
|View full text |Cite
|
Sign up to set email alerts
|

Precautionary behaviours of individuals with multimorbidity during the COVID-19 pandemic

Abstract: Studies show that older individuals with multimorbidity are more susceptible to develop a more severe case of COVID-19 when infected by the virus. These individuals are more likely to be admitted to Intensive Care Units and to die from COVID-19-related conditions than younger individuals or those without multimorbidity. This research aimed to assess whether there are differences in terms of precautionary behaviours between individuals aged 50 + with multimorbidity and their counterparts without multimorbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Although these have been presented as general guidelines for everyone, individuals at greater risk of hospitalization and death when infected by the coronavirus, such as older individuals, have been particularly encouraged to adopt precautionary health behaviors during all phases of the pandemic ( 5 10 ). Monitoring and understanding compliance with COVID-19 preventive behaviors have thus become a prime target for research since the beginning of the pandemic ( 11 18 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these have been presented as general guidelines for everyone, individuals at greater risk of hospitalization and death when infected by the coronavirus, such as older individuals, have been particularly encouraged to adopt precautionary health behaviors during all phases of the pandemic ( 5 10 ). Monitoring and understanding compliance with COVID-19 preventive behaviors have thus become a prime target for research since the beginning of the pandemic ( 11 18 ).…”
mentioning
confidence: 99%
“…Even among older adults, who are at the highest risk of COVID-19 complications, studies have shown that not all individuals follow the recommended precautionary behaviors ( 11 12 ) and/or are vaccinated or willing to be vaccinated ( 23 26 ). Individual sociodemographic characteristics such as gender and education and health conditions are associated with both the adoption of precautionary health behaviors ( 14 18 ) and vaccine acceptance ( 27 30 ). For example, highly educated individuals and those in poorer health conditions were more likely to follow the guidelines and get vaccinated, while a gender “paradox” emerged ( 37 , 38 ): Women are more likely to adopt precautionary behaviors but less likely to accept COVID-19 vaccines.…”
mentioning
confidence: 99%